PENGEMBANGAN TES BERBASIS KOMPUTER - Sri Mulianah; Wahyu Hidayat (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2016)
This study aims to find practical procedure for applying the model to the test on the computer based test methodology of research subjects in order to develop tests in STAIN Parepare.This research method is a method of research and development, namely the development of computer-based test in the of research methodology subject . There are three stages in this study, namely Assembling Problem In Computer Systems, Calibration Test,Utilization In a limited scale .The results of research studies indicate that the development of the test can be done using a computer ( computer base test) . The use of computers as a substitute for tests that use paper and pencil is more efficient and effective.